Цифровізація України та цифровий розвиток - Анісімова, Ольга (Видавництво Львівської політехніки, 2019)
The key aspects of the Concept of development of digital economy and society of Ukraine for 2018-2020 are considered. The directions of digital development are defined. Criteria by which it is possible to define results of digitalization of the Ukrainian society are specified. The purpose of digitalization is formulated. The advantages of the mechanism of digitalization are considered. The list of obstacles to the development of the digital economy in Ukraine has been clarified.
Keywords: цифровізація; цифровий розвиток; цифровий простір; концепція